Efektivitas Therapeutic Group Therapy (TGT) Terhadap Self-Efficacy Pada Remaja: A Systematic Review - Winda Kusumawardani; Bernadetta Germia Aridamayanti; Nursalam Nursalam; Hanik Endang Nihayati (FORIKES, 2020)
Background: The low confidence of adolescents regarding self-ability (low self-efficacy) to complete tasks and challenges will make teens with apathy and pessimism. So that intervention is needed that can provide adolescent stimulus to increase self efficcy, namely Therapeutic Group Therapy (TGT). Objective: To increase self efficcy, namely Therapeutic Group Therapy (TGT). The purpose of this Systematic review is to explain the effectiveness of Therapeutic Group Therapy on self efficcy based on various studies. Method: The author conducted a simple literature review using PRISMA; (1) identified using relevant keywords there were 240 articles selected by meeting the inclusion criteria of 16 articles obtained from several databases including ProQuest, Scopus and ScienceDirect; (2) Articles published between 2012-2019; (3) the area of juvenile nursing and psychology journals. Results: Therapeutic group therapy (TGT) is an effort to promote mental health to increase self-awareness, increase interpersonal relationships, and increase confidence in the ability of adolescents to make changes or all three. There are 10 aspects of development that will be stimulated, including biological, psychosexual, cognitive, moral, spiritual, psychosocial, emotional, language, talent, and creativity aspects. Conclusion: TGT has a significant influence in increasing self-efficacy which enables adolescents to complete developmental tasks in their phase. Implications: To add to the literature review related to therapy for stimulation of development in adolescents. Keywords: therapeutic group therapy; self efficacy; adolescents ABSTRAK Latar belakang: Rendahnya keyakinan remaja tehadap kemampuan diri (self efficacy rendah) untuk menyelesaikan tugas dan tantangan akan menjadikan remaja dengan sikap apatis dan pesimis. Sehingga diperlukan intervensi yang dapat memberikan stimulus remaja untuk meningkatan self efficcy yaitu Therapeutic Group Therapy (TGT). Tujuan: Untuk meningkatan self efficcy yaitu Therapeutic Group Therapy (TGT). Tujuan dari Systematic review ini adalah untuk menjelaskan efektivitas Therapeutic Group Therapy terhadap self efficcy berdasarkan berbagai penelitian. Metode: Penulis melakukan kajian literatur secara sederhana menggunakan PRISMA; (1) diidentifikasi dengan menggunakan kata kunci yang relevan terdapat 240 artikel diseleksi dengan memenuhi kriteria inklusi 16 artikel yang diperoleh dari beberapa database antara lain ProQuest, Scopus dan ScienceDirect; (2) Artikel diterbitkan antara tahun 2012-2019; (3) area jurnal keperawatan dan Psikologi remaja. Hasil: Theraputic group therapy (TGT) merupakan salah satu upaya promosi kesehatan jiwa untuk meningkatkan kesadaran diri (self awereness), meningkatkan hubungan interpersonal, dan meningkatkan keyakinan atas kemampuan yang dimiliki oleh remaja untuk membuat perubahan atau ketiga-tiganya serta terdapat 10 aspek perkembangan yang akan di stimulasi meliputi aspek biologi, psikoseksual, kognitif, moral, spiritual, psikososial, emosi, bahasa, bakat dan kreativitas. Simpulan: TGT memiliki pengaruh yang signifikan dalam meningkatkan self efficacy yang membuat remaja dapat menyelesaiakn tugas perkembangan pada fasenya. Implikasi: Untuk menambah kajian literatur terkait terapi untuk stimulasi perkembangan pada remaja. Kata kunci: therapeutic group therapy; self efficacy; remaja